2020
DOI: 10.1021/acs.analchem.0c02405
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Accuracy of an Analytical Method In Silico: Application to “Accurate Constant via Transient Incomplete Separation” (ACTIS)

Abstract: Analytical methods may not have reference standards required for testing their accuracy. We postulate that accuracy of an analytical method can be assessed in the absence of reference standards in silico if the method is built upon deterministic processes. A deterministic process can be precisely computer-simulated thus allowing virtual experiments with virtual reference standards. Here, we apply this in silico approach to study "Accurate Constant via Transient Incomplete Separation" (ACTIS), a method for find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…The deterministic nature of ACTIS allowed us to create a virtual ACTIS instrument in silico and study the accuracy of ACTIS by computer modeling. 7 This study proved that the accuracy of ACTIS was not affected by large variations in the geometry of the fluidic path and/or the parameters characterizing the flow. The in-silico study led to several important conclusions.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…The deterministic nature of ACTIS allowed us to create a virtual ACTIS instrument in silico and study the accuracy of ACTIS by computer modeling. 7 This study proved that the accuracy of ACTIS was not affected by large variations in the geometry of the fluidic path and/or the parameters characterizing the flow. The in-silico study led to several important conclusions.…”
supporting
confidence: 53%
“…6 We recently introduced Accurate Constant via Transient Incomplete Separation (ACTIS), a method for finding K d of PL, which was hypothesized to be free of inherent sources of inaccuracy. 7 ACTIS is based on a long-known phenomenon of transient incomplete separation (TIS) of the L from PL in a roundcross-section capillary due to their differential transverse diffusion in a laminar flow with a parabolic velocity profile. 8,9 In ACTIS, a short plug of an equilibrium mixture of P and L in a buffer solution is injected into a capillary prefilled with the pure buffer solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The deterministic nature of ACTIS allowed us to assess its accuracy earlier by using a virtual ACTIS instrument built in COMSOL. 7 Our in-silico study revealed that ACTIS accuracy was not influenced significantly by large variations in the parameters of the fluidic setup: the radius of the separation capillary, the radius and length of the injection loop, and the ramp time of the main pump. 7 This invariance of accuracy is important because it gives flexibility in instrument design, and guarantees that the accuracy will not be affected by deviations in the performance parameters of the key instrument components from their nominal values provided by the manufacturer.…”
mentioning
confidence: 75%
“…The initial understanding was that a physical ACTIS instrument had to support ideal conditions such as (i) a cylindrical shape of the initial sample plug, (ii) a parabolic flow-velocity profile, and (iii) the absence of ramp time in the pressure pulse. 7 Maintaining such ideal conditions would require a complex ACTIS instrument and would not leave flexibility with fluidic path design. The invariance of accuracy demonstrated in silico suggests that an ACTIS instrument can be much simpler than it was thought initially.…”
mentioning
confidence: 99%